Ecological Insights, and Fin Fish Diversity in Carps Spawning Grounds: Case Studies from the Surma River and Tanguar Haor, Bangladesh - Kazi Rabeya Akther; Mohammad Amzad Hossain; Sohel Mian; Nirmal Chandra Roy (Scientifica)
This study aims to provide a thorough ecological understanding of fin fish diversity within carp spawning grounds in the Surma River and Tanguar haor. Over two spawning seasons, this research investigates ecological factors impacting fin fish diversity and abundance in carp spawning grounds of the Surma River and Tanguar haor, emphasizing water quality, habitat features, spawn availability, and environmental influences. Fish spawn samples were collected with eight “Savar nets” at chosen sites and reared in a fiberglass tank at the mini hatchery for species identification. The representative spawn samples were examined under a microscope for preliminary species identification before rearing. The study found that both the Surma River and Tanguar haor offer ideal conditions for carp spawning due to factors such as water quality, natural food availability, habitat suitability, and favorable climatic conditions. The study identified 39 fish species under the 10 fish groups from both locations, with a higher percentage of carp species (31.42%) in the Surma River in 2021 compared to 2022 (22.50%). In Tanguar haor, the percentage of carp species was 7.55% and 6.50% in 2021 and 2022, respectively. The Surma River’s ecological indices (2021-2022) indicated decreased diversity, likely due to environmental degradation, while Tanguar haor showed lower diversity possibly attributable to multiple environmental stressors. The dominant carp species, Labeo calbasu, Labeo bata, and Labeo gonius, were identified in both the Surma River and Tanguar haor. The spawning distribution varied among different locations, with some sites showing a presence of carp species, such as Hajipur T1 in the Surma River and Alam Duar T2 in Tanguar haor. The findings highlight the importance of hydrological and environmental parameters in shaping carp spawning habitat distribution and abundance, contributing to aquatic biodiversity conservation and resource management.